Design and Prototype Implementation of a Web-Based Car Rental Information System using Agile Scrum - Fitto Victorya Harissa (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
This study designs and implements a web-based car rental information system prototype to overcome manual process inefficiencies at the case-study company. Development followed Agile Scrum across several sprints that delivered core features: authentication, online booking, real-time vehicle management, transaction handling, and an integrated payment gateway. The technology stack comprises Laravel, MySQL, and XAMPP in a test environment. An early-stage evaluation was conducted in the partner’s operational setting using black-box testing per use-case scenario, along with measurements of process performance, data-recording accuracy, and user satisfaction. Results show transaction time decreased from 20–30 minutes to 5–10 minutes, recording errors dropped from approximately 10% to <1%, 85% of respondents reported satisfaction with booking convenience, and 90% considered the integrated payment helpful. These findings indicate that the prototype effectively improves operational efficiency and service quality, while underscoring the relevance of Agile practices for dynamic rental business needs. Future work includes standardized usability testing, load testing, and a more comprehensive security assessment.